2017
DOI: 10.1007/s11010-017-3092-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular targets for the immunotherapy of hepatocellular carcinoma

Abstract: Liver cancer is the sixth most common cancer worldwide and 3rd most common cause of cancer-related death. Hepatocellular carcinoma (HCC) represents more than 90% of primary liver cancer and is a major public health problem. Due to the advanced stages of HCC at the time of diagnosis, utilizing the conventional treatment for solid tumors frequently ends with treatment failure, recurrence, or poor survival. HCC is highly refractory to chemotherapy and other systemic treatments, and locoregional therapies or selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 231 publications
0
28
0
Order By: Relevance
“…Increased tumorspecific cytotoxicity has indeed been detected after this type of therapies (124)(125)(126). The potential side effect of this treatment is that the presence of PD-L1 on most of APCs in the liver could actually inhibit the tumor-specific T cell response (127) so one obvious measure would be to combine ablation therapy with PD-1 blockade treatment (128,129). This is currently tested in various clinical trials.…”
Section: Target Microenvironment With Physical Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased tumorspecific cytotoxicity has indeed been detected after this type of therapies (124)(125)(126). The potential side effect of this treatment is that the presence of PD-L1 on most of APCs in the liver could actually inhibit the tumor-specific T cell response (127) so one obvious measure would be to combine ablation therapy with PD-1 blockade treatment (128,129). This is currently tested in various clinical trials.…”
Section: Target Microenvironment With Physical Agentsmentioning
confidence: 99%
“…It is logical to assume that targeting the immune cells in the liver, reverting what cause their anergic state, may offer a solution for cancer treatment. Several immunotherapy trials have been conducted for HCC with cell therapy (LAK and TIL), cytokines and check-point inhibitors, dendritic cells vaccines and combinations of the above (129). The outcomes of these trials are promising but still not enough to offer a complete remission for HCC.…”
Section: Target Microenvironment With Immunotherapymentioning
confidence: 99%
“…Unlike certain other malignancies, HCC cells do not appear to be inherently immunogenic. However, recent papers that studied checkpoint inhibitors for HCC demonstrated promising results, 52 53 and more phase I and II clinical studies are underway to investigate the effects of various immune checkpoint inhibitors, including cytotoxic T-lymphocyte-associated protein-4 inhibitors and anti-programmed death-1 (anti-PD-1) antibody. Nevertheless, modest response rates have indicated that the efficacy of these checkpoint inhibitors appears to be insufficient.…”
Section: A New Role For Stereotactic Body Radiotherapy As An Immunostmentioning
confidence: 99%
“…And, several pan-HDAC inhibitors, such as sodium valproate, etinostat, panobinostat, and vorinostat, have all been shown in vivo to enhance the antitumor efficacy of checkpoint inhibitory antibodies, as well as promote activated T cell infiltration into the tumors (Booth, Roberts, Poklepovic, & Dent, 2017; Booth, Roberts, Poklepovic, Kirkwood, & Dent, 2017; Christiansen et al, 2011; Gameiro, Malamas, Tsang, Ferrone, & Hodge, 2016; Hornig, Heppt, Graf, Ruzicka, & Berking, 2016; Kroesen et al, 2016; Vo et al, 2009; West & Johnstone, 2014; West et al, 2013). Tumor types tested in these studies are diverse and include melanoma, breast, colorectal, glioblastoma, and hepatoma (Chae, Wang, Nimeiri, Kalyan, & Giles, 2017; Huang et al, 2017; Keller, Zhang, Li, Schaider, & Wells, 2017; Monnot & Romero, 2017; Rai et al, 2017). …”
Section: Text Elementsmentioning
confidence: 99%